INSIG1 infl uences obesity-related hypertriglyceridemia in humans - Smith, E.; Zhang, Y.; Baye, T.; Gawrieh, S.; Cole, R.; Blangero, J.; Carless, M.; Curran, J.; Dyer, T.; Abraham, L.; Moses, Eric; Kissebah, A.; et al. (American Society for Biochemistry and Molecular Biology, Inc., 2010)
In our analysis of a quantitative trait locus (QTL) for plasma triglyceride (TG) levels [logarithm of odds (LOD) = 3.7] on human chromosome 7q36, we examined 29 single nucleotide polymorphisms (SNPs) across INSIG1, a biological candidate gene in the region. Insulin-induced genes (INSIG s) are feedback mediators of cholesterol and fatty acid synthesis in animals, but their role in human lipid regulation is unclear. In our cohort, the INSIG1 promoter SNP rs2721 was associated with TG levels (P = 2 × 10 3 in 1,560 individuals of the original linkage cohort, P = 8 × 10 4 in 920 unrelated individuals of the replication cohort, combined P = 9.9 × 10 6). Individuals homozygous for the T allele had 9% higher TG levels and 2-fold lower expression of INSIG1 in surgical liver biopsy samples when compared with individuals homozygous for the G allele. Also, the T allele showed additional binding of nuclear proteins from HepG2 liver cells in gel shift assays. Finally, the variant rs7566605 in INSIG2, the only homolog of INSIG1, enhances the effect of rs2721 (P = 0.00117). The variant rs2721 alone explains 5.4% of the observed linkage in our cohort, suggesting that additional, yet-undiscovered genes and sequence variants in the QTL interval also contribute to alterations in TG levels in humans. Copyright © 2010 by the American Society for Biochemistry and Molecular Biology, Inc.